The microneme protein1 (MIC1) of Chinese 1 Toxoplasma regulates pyroptosis through the TLR4/NLRP3 pathway in macrophages - Wenze Sun; Fan Zhang; Jinjin Zhu; Yanxia Yu; Yang Wang; Qingli Luo; Li Yu (Parasites & Vectors)
Abstract Background TgMIC1, a soluble adhesion protein that typically facilitates parasite invasion, exhibited varying expression levels among distinct virulence strains of Chinese 1 Toxoplasma. This study aims to explore its role in immunological regulation and its association with diverse postinfection outcomes in Toxoplasma infection. Methods First, the mic1 knockout strain Wh3Δmic1 was generated and assessed for its virulence and proliferative capacity. Subsequently, the serum inflammation levels were examined in mice infected with Wh3Δmic1, Wh3, and Wh6. Furthermore, rMIC1 and rMIC1-T126A/T220A, which lack binding sites to N-glycan in TLR4, were produced for coculture with bone marrow-derived macrophages (BMDMs) to investigate their impact on pyroptosis. Results Our data showed Wh3Δmic1 exhibited a significant reduction in invasion efficiency, limited growth, and attenuated inflammatory responses in mice. Additionally, it displayed a decreased capacity to induce pyroptosis when compared with Wh3-infected BMDMs. Moreover, rMIC1 but not rMIC1-T126A/T220A was found to be able to upregulate NOD-like receptor pyrin domain-containing protein 3 (NLRP3) and activate GSDMD and caspase-1 in BMDMs but not in TLR4−/− and NLRP3−/− BMDMs. Conclusions TgMIC1 is implicated in both parasite invasion and the modulation of macrophage pyroptosis via the TLR4/NLRP3 pathway. This investigation indicates that TgMIC1 serves diverse functions in Toxoplasma gondii infection, thereby enhancing comprehension of the immune regulatory mechanisms of the parasite. Graphical Abstract